The Colombian Migrants in the Colombian Press: A Lecture of Gender: 1990–2006 - Bazurto Botero, Victoria Elena (Sociedad y Economía, 2015)
The following article has the goal of identify the representations created through the discourse of the newspapers El Tiempo and El Espectador around the Colombian women emigrating to Spain. To that end, the articles published in these newspapers from January 1st, 1990 to December 31st, 2006 were analyzed. Despite recognizing the importance of women within the Colombian migration phenomenon, an inadequate discourse remains in the newspapers in which predominate the generic male form. Furthermore, the positive cultural representations given to them appear to be in very low numbers as opposed to those that designate them as responsible of family breakdown and as victims of human trafficking and people smuggling.